A Comprehensive Framework to Optimize Short-Term Experiences in Global Health (STEGH) - Shivani Shah; Henry C. Lin; Lawrence C. Loh (BMC, 2019)
Abstract Increasing demand for Short-term Experiences in Global Health (STEGH), particularly among medical trainees, has seen a growth in programming that brings participants from high-income countries to low and middle-income settings in order to engage in service, teaching or research activities. Historically the domain of faith-based organizations conducting "missions", STEGH are now offered by diverse groups including academic institutions, non-profit organizations, and the private sector, either as dedicated for-profits or through corporate social responsibility arms. The growing popularity of STEGH has resulted in concerns about their negative impacts on host communities. Traditional STEGH are often crafted with little or no input from host community leaders, and this results in activities that do not address locally identified priorities. Other concerns include culturally incongruent programming and the creation of parallel systems that disrupt established local services and redirect scarce local resources, which fosters dependency instead of building capacity. One concern specific to trainees also includes trainee provision of services beyond their scope and training level. To address these concerns, this paper presents a comprehensive framework that aims to categorize promising interventions that might promote greater responsibility in STEGH. Based on the micro-meso-macro framework, this paper proposes various interventions as incentives and disincentives to be deployed at the individual, program, and societal levels to promote greater responsibility in STEGH. Deployed altogether, the interventions contemplated by this framework would foster the optimal context  required to encourage responsibility, minimize harms, and optimize host community outcomes for STEGH.